GAYA KEPEMIMPINAN, MOTIVASI KERJA, DISIPLIN KERJA DAN KINERJA STUDI KASUS TERHADAP PEGAWAI TIDAK TETAP DI SMP NEGERI 4 PAKEM - KURNIA ASTIANI (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2019)
Abstract This research is aimed to examine and analyze the difference of the principal leadership style, compare the work motivation, discipline and performance of honorary employees of SMP Negeri 4 Pakem, and find out whether the work motivation, discipline and performance of the honorary employee of SMP Negeri 4 Pakem have fulfilled the school need or not. The analysis method is conducted through questionnaires and given to the 16 honorary employees of SMP Negeri 4 Pakem. The data analysis on this study uses the help of SPSS version 16. The technique applied in this study uses editing in which editing is the process of checking and adapting the obtained study data. Coding is a marking activity in the form of numbers on the questionnaire answers to be classified into the same category. Scoring is changing the qualitative data into the quantitative one. Tabulating presents the obtained data in tables. Conclusion is to conclude the presented SPSS result. The analysis result shows that, first, the leadership styles of the principals of SMP Negeri 4 Pakem are different. WoroTriwulanAmbarwati has paternalistic leadership style and Ponidi applies democratic leadership style. Secondly,there is a difference in the work motivation, discipline and performance of honorary employees in conducting jobs. The third is that the motivation, discipline and performance conducted by the honorary employees have fulfilled the school need to improve the school. Key words: Leadership Style, Motivation, Discipline, Performance and Honorary Employee